Rationalising factors influencing the effective utilisation of big data in Malaysian fintech companies - Ibrahim Ahmed, Ibrahim Nasreldin; Abdullah, Lili Marziana; Mohd Nor, Rizal (New Millennium Discoveries, 2023)
In Malaysia, Fintech companies are leveraging Big Data technology to serve effectively the targeted markets. As the financial industry continues to develop, there is a great potential for the further growth and use of Big Data in Fintech in Malaysia. This is an exploratory study which is set to identify factors that influence the use of Big Data in the Fintech sector. Using a systematic selection process, publications related to Big Data adoption were identified and reviewed. The results show that the technological, organisational and environmental factors have a clear impact on Big Data adoption. The paper also presents the challenges reflected on in the current research on Big Data adoption and recommends future research directions. A research model focused on utilisation of Big Data technology is proposed and presented, driven by the literature review.